Flutter Regularity of Flying Wing Configuration with All-Moving Wing Tip - Wei-ji WANG; Wei QIAN; Xiang HE; Xin-yu AI; Zheng CHEN (气体物理, 2023)
The performance requirements of modern fighters meet multiple targets such as high speed, high mobility, stealth, lightweight and so on. The aircraft with a tailless flying wing configuration has the advantages of high aerodynamic efficiency, good mobility, low detectability, and flying integration. Such configuration adopts a structural design with wing and body fusion, multi-control surface and all-moving wing tip. The innovative structure of the wing tip highlights its aeroelasticity problem, in which the coupling effect between the structure of wing tip and the control surface makes the flutter behavior particularly prominent. This paper adopted the linear flutter method and the mode tracking method to study the flutter problem of all-moving wing tip. According to the study, the flutter coupling has three types for the aircraft with a tailless flying wing configuration: coupling between the first symmetrical bending of wing and the symmetric rotation of all-moving wing tip (symmetrical couple), coupling between the first anti-symmetrical bending of wing and the anti-symmetric rotation of all-moving wing tip (antisymmetric couple) and the fuselage mode in flutter. It is found that the flutter speed of the antisymmetric coupling type is lower than that of the symmetric coupling type. From the flutter result, the coupling flutter speed of the fuselage and wing is higher than that of the former two, and the coupling speed of the fuselage and the all-moving wing tip is lower than that of the former two. The main structural factors affecting the symmetric coupled flutter are wing bending stiffness and rotational stiffness of the all-moving tip, while the main structural factors affecting the antisymmetric coupled flutter are wing bending stiffness, fuselage rotational inertia and rotational stiffness of the all-moving tip. The all-moving wing tip structure is the internal factor that makes the tailless flying wing prone to flutter.